The Effects of Microwave Curing on Dielectric Properties of Banana Fiber Reinforced High-Density Polyethylene Composite - Sie Ming, Tasha Lai; Jayamani, Elammaran; Heng , Soon Kok; Subramanian, Jeyanthi (Applied Science and Engineering Progress, 2024)
This study investigates the dielectric properties of banana fiber reinforced high-density polyethylene composites, both with and without magnesium oxide (MgO) as conductive filler, utilizing microwave curing. Dielectric properties play a crucial role in the design and performance of materials in various fields, including electronics and energy storage systems. The introduction of MgO as a conductive filler significantly enhances the dielectric constant of the composites, resulting in improved electrical energy storage capacity. Microwave curing emerges as a key factor in enhancing dielectric properties. Compared to conventional oven and room temperature curing techniques, microwave cured composites consistently exhibit higher dielectric constants. The dielectric constant of 0.24 at 2 MHz for microwave cured NaOH treated fibers. In addition, the comparison of dielectric permittivity made from oven-cured and microwave-cured composites at relaxation frequencies of 10 kHz exhibited an 11 percent increase through microwave curing. The rapid and volumetric heating properties of microwave curing enable more effective dispersion and distribution of MgO particles within the composites, ultimately enhancing interfacial polarization and dielectric performance.